The Influence of Self-Regulation, Homesickness, and Culture Shock on Migrant Students' Self-Adjustment - Suandara Pratiwi; Budi Astuti; Kasmi Kasmi; Meldi Latifah Saraswati (Journal of Innovation in Educational and Cultural Research, 2025)
Migrant students need adjustments to their new environment. Yogyakarta is one of the cities that prospective students can visit to continue their education. With the culture in Yogyakarta, migrant students need self-adjustment skills to balance life in society and university. This study aims to analyze the influence of self-regulation, homesickness, and culture shock on the self-adjustment of first-year migrant students in Yogyakarta. The method used is a quantitative correlation with an infinite population and a sample of 349 people. Data collection uses a self-regulation scale, homesickness scale, culture shock scale, and self-adjustment scale, with data analysis using multiple linear regression analysis accompanied by classical assumption tests. This study concludes that self-regulation, homesickness, and culture shock significantly influence the self-adjustment of first-year migrant students in Yogyakarta, where conceptually, each variable has a positive and negative influence that affects one another. In this study, self-regulation has a positive influence. In contrast, homesickness and culture shock have a negative influence, which means that the better a person's self-regulation, the more homesickness decreases, and the more culture shock a person feels, the better a person's self-adjustment.  From these findings, it is also hoped that new students, especially students who have just migrated to an area, can optimize their abilities by being aware of themselves and their environment. Adjustment speed and accuracy are needed to facilitate activities in the community and the college environment so that new students can adapt well and optimize their abilities.